Fluid teams in the metaverse: exploring the (un)familiar - Jarvenpaa, Sirkka L.; Keating, Elizabeth (Frontiers in Psychology, 2024)
The metaverse is a new and evolving environment for fluid teams and their coordination in organizations. Fluid teams may have no prior familiarity with each other or working together. Yet fluid teams are known to benefit from a degree of familiarity–knowledge about teams, members, and working together–in team coordination and performance. The metaverse is unfamiliar territory that promises fluidity in contexts–seamless traversal between physical and virtual worlds. This fluidity in contexts has implications for familiarity in interaction, identity, and potentially time. We explore the opportunities and challenges that the metaverse presents in terms of (un)familiarity. Improved understandings of (un)familiarity may pave the way for new forms of fluid team experiences and uses.